2018
DOI: 10.3171/2016.10.jns161042
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography angiography as a confirmatory test for the diagnosis of brain death

Abstract: OBJECTIVE For a diagnosis of brain death (BD), ancillary testing is performed if patient factors prohibit a complete clinical examination and apnea test. The American Academy of Neurology (AAN) guidelines identify cerebral angiography (CA), cerebral scintigraphy, electroencephalography, and transcranial Doppler ultrasonography as accepted ancillary tests. CA is widely considered the gold standard of these, as it provides the most reliable assessment of intracranial blood flow. CT angiography (CTA) is a noninva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…The MCA-M4, ICV, and VG were also sensitive for diagnosing brain death. 11,17 This is thought to be due to the increased intracranial pressure, resulting in increased cerebral vascular resistance and compression of intracranial vessels. 11 There were many limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…The MCA-M4, ICV, and VG were also sensitive for diagnosing brain death. 11,17 This is thought to be due to the increased intracranial pressure, resulting in increased cerebral vascular resistance and compression of intracranial vessels. 11 There were many limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that in a patient with clinical diagnosis of BD, observation of intracranial circulatory arrest or non-filling can confirm the diagnosis of BD. A recent study performed in 18 patients showed a 75% sensitivity, a specificity and positive predictive value of 100%, and a 33% negative predictive value for CTA [ 20 ]. The 100% specificity observed in ours and the other study suggests that when the previously described positive findings are observed on CTA, the diagnosis of BD can reliably be confirmed without the need for further ancillary studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Garret et al assessed statistical performance of CTA in diagnosing brain death. For all the 18 patients included in the study, CTA had sensitivity of 75%, specificity of 100%, positive predictive value of 100%, and negative predictive value of 33% [15]. Another recent study from Macdonald et al reported the diagnostic accuracy and inter-rater reliability of different ancillary imaging tests used for brain death in 74 patients.…”
Section: Computed Tomography Angiography (Cta)mentioning
confidence: 95%